Peroxiredoxin 6 modulates Toll signaling pathway and protects DNA damage against oxidative stress in red swamp crayfish (Procambarus clarkii). Issue 89 (June 2019) - Chu, Sheng-Hui; Liu, Li; Abbas, Muhammad Nadeem; Li, Yan-Yan; Kausar, Saima; Qian, Xing-Yi; Ye, Zhi-Ze; Yu, Xiao-Min; Li, Xiao-Kun; Liu, Min; Dai, Li-Shang
Abstract: Peroxiredoxin 6 (Prx6) is an important member of the peroxiredoxin family that plays critical roles in protecting host against the toxicity of oxidative stress and participates in cell signaling. Herein, we report Prx6 gene from red swamp crayfish, Procambarus clarkii . The cDNA fragment of PcPrx6 was 660 bp, encoding a 219 amino acid residues protein. The quantitative real time PCR analysis showed ubiquitous expression of PcPrx6 mRNA in the tested tissues. The challenge with peptidoglycan and Poly I:C remarkably suppressed the mRNA level of PcPrx6 in hepatopancreas at 3, 12, 48 h compared with the PBS control. However, the expression level significantly increased after 36 h of their treatment. The knockdown of PcPrx6 by small interference RNA significantly enhanced the transcript levels of Toll pathway-responsive genes at 24 h. Recombinant PcPrx6 protein was purified using affinity chromatography and analyzed for its biological role. The results revealed that the recombinant PcPrx6 protein manifested the ability to protect supercoiled DNA damage from oxidative stress elicited by mixed function oxidative assay. Altogether, PcPrx6 may have multiple functional roles in the physiology of P. clarkii, since it negatively regulates the Toll signaling transduction and protects supercoiled DNA damage from oxidative stress. Highlights: Peroxiredoxin 6 from Procambarus clarkii was identified and characterized for the first time. The PcPrx6 expression in the hepatopancreas was up-regulated post PGN and Poly I:C challenge. We investigated the antioxidant role of recombinant PcPrx6 protein in vitro by mixed-function oxidase assay. RNA interference of PcPrx6 affected the gene expression of members of the Toll pathway.